Hubungan Pengetahuan Perawat tentang Supervisi dengan Kemampuan Melaksanakan Pendokumentasian Asuhan Keperawatan - Tumanggor, Rustiana; Tanjung, Riswani; Fujiati, Isti Ilmiati (Journal of Telenursing (JOTING), 2023)
This study aims to analyze nurses' knowledge about supervision and their ability to carry out documentation of nursing care at Murni Teguh Hospital, Medan. This type of research uses a cross sectional approach design. With this type of observational research, quantitative approach. The instruments used in this research were questionnaires and patient care documents from medical records. The research results showed that there was a relationship between nurses' knowledge about supervision and nurses' ability to carry out nursing care documentation, with a value of p = 0.004. In conclusion, nurses' knowledge about supervision at Murni Teguh Hospital in Medan is still lacking, so based on the results of statistical tests it was found that there was a relationship between knowledge about documentation and the ability to carry out documentation. Keywords: Knowledge, Documentation, Supervision.